The Role Of Work Competence, Motivation, And Work Environment In Improving Employee Performance - I Ketut Setia Sapta; I Wayan Gunantra; I Wayan Widnyana (Journal of Business and Behavioural Entrepreneurship, 2022)
ABSTRACT Competence and motivation do not necessarily improve or worsen employee performance; even working environment not only might be excessive but also might have less attention. This study aimed at exploring the changing role of working competence, motivation and environment to produce business value in achieving the excellent employee performance. This study was conducted at the Regional Planning, Research and Development Board in Tabanan Regency with a population of 80 employees by applying a sampling technique with saturated samples. The findings of this study led the results of increasing competence actually worsened the performance. However, motivation in carrying out work improved the performance due to wholeheartedly working performance and the employees realized about taking part in the work so that it can affect the performance of the organization itself. Meanwhile, good competence here meant the quality of building good working environment as positive and significant as the working motivation. Taking into account, condusive working environment encouraged employee performance in carrying out the work. Keywords : Work Competence; Motivation; Work Environment; Employee Performance